Alcohol-based hand sanitizer use among university students in Bangladesh: knowledge, practices, and influencing factors - Islam, Md Ekhtekharul; Chowdhury, Monsur; Hassin, Fahmida; Rahman, Hafizur; Ara, Kulsum (International Journal of Public Health Science (IJPHS), 2025)
Since the outbreak of the novel coronavirus epidemic in December 2019, it has become a significant threat to the health and lives of the global population. In 2020, the World Health Organization (WHO) approved alcohol-based hand sanitizer (ABHS) as an alternative hand hygiene method to prevent the spread of coronavirus infection. As a result, during the COVID-19 epidemic, the use of alcohol-based hand sanitizers expanded rapidly, particularly among students. In Bangladesh, there has been a substantial growth of ABHS producers since the outbreak of coronavirus. Greater emphasis was placed on the necessity to use ABHS for protection but but placed less emphasis on safe use. This research attempts to assess the knowledge, practices, and influencing factors related to ABHS usage among university students in Dhaka, Bangladesh. A cross-sectional online survey was carried out among 800 university students using a semi-structured questionnaire. More than half of the students buy alcohol-based hand sanitizer due to their effectiveness. The multiple regression analysis suggests that age, sex, and family income sources have affected students' knowledge and practice scores associated with alcohol-based hand sanitizers. This study highlights the need for proper ABHS usage, handling, and selection for maximum efficacy against targeted infections and safe ABHS use. Only adequate awareness and knowledge on hand hygiene practices can reduce the risks of pathogen transmission, either directly or indirectly.